Currículo e Cultura de Consumo: como jovens estudantes significam o consumo no espaço-tempo escolar - Balinhas, Vera Lúcia Gainssa (2008)
In this dissertation it is presented reflections about consumerism and its meaning to a group of sixteen high school students from a public school of Rio Grande, Cassino, Rio Grande do Sul state. The investigative process was taken through joint and also individual meetings which tried to investigate the students consumerism at school. Some tools were selected to stimulate the debate, tools like diaries, drawings, artistic installation, visits to McDonald´s and documentaries. Being a teacher at a school allowed me to be in contact with the ethnographic research. In the analyses of consumerism and its meanings for students it was used theoretical support of authors such as Michel Foucault, Mike Featherstone, Nestor Canclini, Jean Baudrillard, Ivor Goodson, Stuart Hall and Tomaz Tadeu da Silva. While discussing consumerism patterns the research pointed out some transgressions on the way the studied group consumes. This transgression is understood as a movement that changes - moves and dislodges the limits whether they are regarded as norms, moral conducts or habits. Furthermore, the consumerism also constitutes identity as a marker, used to gain status, recognition, pleasure, communicate tastes and lifestyles. Finally, it is suggested the school as a possible place to rethink the consumerism culture beyond the ordinary market of nowadays.